2010
DOI: 10.1161/strokeaha.109.573402
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcome of a Stroke Cohort in Martinique, French West Indies

Abstract: Background and Purpose-Limited information exists on stroke among black populations outside the United States and United Kingdom. Part 1 of the Etude Réalisée en Martinique et Centrée sur l'Incidence des Accidents vasculaires cérebraux (ERMANCIA) provided strong epidemiologic data on the incidence of first-ever stroke in a black Caribbean population and showed a 40% greater incidence of stroke in Martinique than in continental France. In ERMANCIA part 2, we evaluated the long-term outcomes of our cohort. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
(32 reference statements)
0
26
0
2
Order By: Relevance
“…Data from our analyses confirm fluctuation in rates of depression over 10 y, with an average of 31% of patients having depression. In Martinique, depression at 5 y after stroke was estimated at 25.8%, using the Montgomery-Asberg Depression Rating Scale [41].…”
Section: Discussionmentioning
confidence: 99%
“…Data from our analyses confirm fluctuation in rates of depression over 10 y, with an average of 31% of patients having depression. In Martinique, depression at 5 y after stroke was estimated at 25.8%, using the Montgomery-Asberg Depression Rating Scale [41].…”
Section: Discussionmentioning
confidence: 99%
“…33 The associations between depression and stroke severity, impaired cognition, dependence, low activity levels, and social isolation had been observed only soon after stroke. 2,4 -12,33,34 Unlike many studies, [2][3][4][5][6][7][8][9][10][11][12][13][14]17,20 treatment for depression predicted depression 3 months and 5 years after stroke. Factors involved in the etiology of depression before stroke that are still present after the event may explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6 Independent of the timing and instrument used for assessment, previous reports of depression among African American stroke survivors range from 10.2 to 43.9%. 3, 710 Although depression among African American stroke survivors negatively impacts overall health and quality of life, 11, 12 the association with functional recovery is unclear.…”
mentioning
confidence: 99%
“…Of these 15, seven studies reported depression specifically among Africa American stroke survivors of which only 4 studies reported function. 3,79 However, no studies to date have specifically measured depression and functional status among African American stroke survivors who receive inpatient rehabilitation. There is a significant lack of knowledge of the prevalence of depression among African American stroke survivors and the association of their depression with functional outcomes.…”
mentioning
confidence: 99%